2014
DOI: 10.1111/jth.12574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant ADAMTS‐13 on microthrombosis and brain injury after experimental subarachnoid hemorrhage

Abstract: To cite this article: Vergouwen MDI, Knaup VL, Roelofs JJTH, de Boer OJ, Meijers JCM. Effect of recombinant ADAMTS-13 on microthrombosis and brain injury after experimental subarachnoid hemorrhage. J Thromb Haemost 2014; 12: 943-7.Summary. Background: A common complication after aneurysmal subarachnoid hemorrhage (SAH) is delayed cerebral ischemia (DCI), which is associated with vasospasm and other mechanisms such as microthrombosis. ADAMTS-13 activity plays a role in the prevention of thrombus formation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
1
28
1
1
Order By: Relevance
“…In in vivo studies, ADAMTS‐13 was defined to play a protective role in ischemia‐reperfusion brain damage . In addition to this, in mice with subarachnoid hemorrhages, treatment with recombinant ADAMTS‐13 induces statistically significant reductions in the areas of microthrombi and damaged brain tissue . In addition to this information, in the experimental stroke models, ADAMTS‐13 deficiency was shown to exacerbate neuronal damage and addition of exogenous ADAMTS‐13 attenuates the condition and elevates the healing process .…”
Section: Discussionsupporting
confidence: 54%
“…In in vivo studies, ADAMTS‐13 was defined to play a protective role in ischemia‐reperfusion brain damage . In addition to this, in mice with subarachnoid hemorrhages, treatment with recombinant ADAMTS‐13 induces statistically significant reductions in the areas of microthrombi and damaged brain tissue . In addition to this information, in the experimental stroke models, ADAMTS‐13 deficiency was shown to exacerbate neuronal damage and addition of exogenous ADAMTS‐13 attenuates the condition and elevates the healing process .…”
Section: Discussionsupporting
confidence: 54%
“…Two recent studies showed that recombinant ADAMTS13 reduces microthrombosis and brain injury after experimental SAH. [40][41] ADAMTS13 rapidly cleaves ultralarge vWF multimers, reduces platelet adhesion and aggregation, and downregulates inflammation and thrombus formation. [42][43][44][45] In stroke models, recombinant ADAMTS13 did not affect bleeding rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a few studies have been performed evaluating ADAMTS13 levels in patients with ischemic stroke, a meta-analysis of 616 patients demonstrated a clear association between reduced ADAMTS13 levels and increased risk of stroke [OR 2.72; 95% CI (1.52 – 4.86)] (2). Experimental murine models of SAH demonstrate that Adamts13 −/− mice sustain larger areas of microvascular thrombosis than do wild-type mice, but that with recombinant ADAMTS13 treatment, the knock out mice can experience smaller thrombosis areas, similar to wild type mice (45). Therefore, recombinant ADAMTS13 may be a putative treatment option in SAH patients at risk for DCI.…”
Section: Discussionmentioning
confidence: 99%